Use of a lignocellulosic residue as solid fuel: The effect of ash content in the energy potential - Santiago Hansted, Ana Larissa [UNESP]; Cacuro, Thiago Aguiar; Nakashima, Gabriela Tami; Costa, Vladimir Eliodoro [UNESP]; Yamamoto, Hiroyuki; Yamaji, Fabio Minoru (Elsevier B.V., 2018)
Bark is a residue that can be used as fuel by the industry. One of the problems of its use is the impurity that it may contain. This study aimed to characterize physically and thermo-chemically the eucalyptus bark used as a fuel in a wood panel industry, relating the high heating value (HHV) with the ash content. Six treatments were provided according to particle size and washing process of the bark: T1 (850 mu m to 425 mu m/unwashed), T2 (retained on 250 mu m/unwashed), T3 (< 150 mu m/unwashed), T4 (850 mu m to 425 mu m/washed), T5 (retained on 250 mu m/washed), T6 (< 150 mu m/washed). The material was assessed regarding moisture content. The treatments were subjected to HHV and proximate analysis. The ashes were analyzed under SEM-EDS to identify the components/impurities. The data obtained in this study were statistically analyzed using the software R. The material presented moisture content of 70% on a dry basis, which is considered high for use in bioenergy. It was identified the presence of silica and calcium in the ash, which indicates the presence of soil in the material. The process of washing the bark was efficient for the reduction in ash content only in particle size < 150 mu m. The separation of the bark in particle size was a better technique to reduce the impurities. The proximate analysis showed a significant difference among treatments. The ash content presented values from 2.63% (T1) to 13.86% (T3). The HHV was 18 828 J g(similar to 1) (T1) and 15 757 J g(similar to 1)(T3). The separation in particle size reduced 81.02% in the ash content, which represented an increase of 21.05% in the HHV. This result showed the effect of the ash content in the energy potential.
Keywords: Biomass; Bioenergy; Bark; Eucalyptus; High heating value